National Security Issues in Science, Law, and Technology, 1st edition - Johnson, Thomas A. (CRC Press, 2020)
The tragedy of 9/11 placed homeland security and the prevention of further attacks into the central focus of our national consciousness. With so many avenues of terror open to our enemies in terms of mode, medium, and location, effective management and mitigation of threat must be grounded in objective risk assessment.